2014
DOI: 10.1111/jcpt.12148
|View full text |Cite
|
Sign up to set email alerts
|

Safety profiles of adalimumab, etanercept and infliximab: a pharmacovigilance study using a measure of disproportionality in a database of spontaneously reported adverse events

Abstract: Although the disproportionalities found for adalimumab and etanercept may suggest strong associations with particular adverse events, caution is needed when drawing conclusions on the association between infliximab and the adverse events analysed. In the light of the present findings, these results deserve further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
3
18
0
1
Order By: Relevance
“…In our study, 28% of patients presented side effects, needing treatment interruption for half of them. In line with previous studies on BD [8] or other inflammatory diseases [47,48], infections were the most frequent side effects. Safety issues were similar between anti-TNF agents used, which was previously noted in other studies in autoimmune diseases like psoriatic arthritis [49].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 28% of patients presented side effects, needing treatment interruption for half of them. In line with previous studies on BD [8] or other inflammatory diseases [47,48], infections were the most frequent side effects. Safety issues were similar between anti-TNF agents used, which was previously noted in other studies in autoimmune diseases like psoriatic arthritis [49].…”
Section: Discussionsupporting
confidence: 89%
“…We also observed several cases of neoplasia and autoimmune disease. A pharmacovigilance study of the safety of anti‐TNF in uveitis demonstrated increased risk of infection, autoimmune disease, and neoplasia with IFX and ADA treatment . Similar results have been reported with regard to IFX and ADA treatment of other inflammatory diseases .…”
Section: Discussionsupporting
confidence: 69%
“…From these preliminary results, it appears that these drugs have similar safety profiles, with the most frequently reported adverse events being nasopharyngitis, upper respiratory infections, headache, and injection site reaction (Mansouri and Goldenberg, 2015). These adverse events are similar to those seen in older biologic agents such as adalimumab, etanercept, and infliximab (Mendes et al, 2014). …”
supporting
confidence: 67%